2017
DOI: 10.1111/jnc.14004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for purine nucleoside phosphorylase (PNP) release from rat C6 glioma cells

Abstract: Intracellular purine turnover is mainly oriented to preserving the level of triphosphate nucleotides, fundamental molecules in vital cell functions that, when released outside cells, act as receptor signals. Conversely, high levels of purine bases and uric acid are found in the extracellular milieu, even in resting conditions. These compounds could derive from nucleosides/bases that, having escaped to cell reuptake, are metabolized by extracellular enzymes similar to the cytosolic ones. Focusing on purine nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…This suggested that the levels of extracellular guanine-based purines depended both on the balance between nucleotide release and nucleoside uptake and on the presence, in the culture medium, of extracellular purine-converting enzymes. Indeed, by using Immunoblot analysis and HPLC for the measurement of the enzyme activities ( Giuliani et al, 2017 ), we confirmed the presence in the culture medium of PNP and GDA ( Figure 1C ). Both the enzymes tended to accumulate in the culture medium over the time (from 2 up to 12 h) following a similar trend even though at different levels (PNP amount was about 7–10 fold higher than GDA).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…This suggested that the levels of extracellular guanine-based purines depended both on the balance between nucleotide release and nucleoside uptake and on the presence, in the culture medium, of extracellular purine-converting enzymes. Indeed, by using Immunoblot analysis and HPLC for the measurement of the enzyme activities ( Giuliani et al, 2017 ), we confirmed the presence in the culture medium of PNP and GDA ( Figure 1C ). Both the enzymes tended to accumulate in the culture medium over the time (from 2 up to 12 h) following a similar trend even though at different levels (PNP amount was about 7–10 fold higher than GDA).…”
Section: Resultsmentioning
confidence: 53%
“…According to the method previously described ( Giuliani et al, 2012 , 2017 ), purines were measured by an Agilent 1100 series HPLC system (Agilent Technologies, Santa Clara, CA, United States), by using, for the separation of the compounds, a reverse phase analytical column (LiChrospher 100 RP-18 5 μm in LiChroCART 125-4, Merck) and a 15-min linear gradient [from 100% of buffer A (60 mM KH 2 PO 4 and 5 mM tetrabutylammonium phosphate, pH 6.0) to 100% solvent B (30% methanol plus 70% buffer A)] at a flow rate of 1.5 mL/min. The detection of unlabeled compounds was achieved using a Diode Array Detector (Agilent Technologies, Santa Clara, CA, United States) with wavelength set at 254 nm for all the substances except Uric Acid (UAc), which was 290 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P2X7R antagonists blocked the cell cytotoxicity caused by irradiation for glioma ( Gehring et al, 2015 ). Purine nucleoside phosphorylase is released from rat C6 glioma cells, contributing to the purinergic system homeostasis and exhibiting a pathophysiological role ( Giuliani P. et al, 2017 ).…”
Section: Disorders Of the Central Nervous System (Cns)mentioning
confidence: 99%
“…Samples containing PNP were obtained as described by Giuliani et al (2017). Briefly, SH-SY5Y cells were incubated in serum-free medium without or with 100 µM GUO.…”
Section: Measurement Of Extracellular Guanosine and Guanine Levels And Enzyme Activity Assaymentioning
confidence: 99%